High-efficiency purification of divergent AAV serotypes using AAVX affinity chromatography - Michael Florea; Fotini Nicolaou; Simon Pacouret; Eric M. Zinn; Julio Sanmiguel; Eva Andres-Mateos; Carmen Unzu; Amy J. Wagers; Luk H. Vandenberghe (Molecular Therapy: Methods & Clinical Development, 2023)
The adeno-associated viral vector (AAV) provides a safe and efficient gene therapy platform with several approved products that have marked therapeutic impact for patients. However, a major bottleneck in the development and commercialization of AAV remains the efficiency, cost, and scalability of AAV production. Chromatographic methods have the potential to allow purification at increased scales and lower cost but often require optimization specific to each serotype. Here, we demonstrate that the POROS CaptureSelect AAVX affinity resin efficiently captures a panel of 15 divergent AAV serotypes, including the commonly used AAV2, AAV8, AAV9, PHP.B, and Anc80. We also find that AAVX resin can be regenerated repeatedly without loss of efficiency or carry-over contamination. While AAV preps purified with AAVX showed a higher fraction of empty capsids than preps purified using iodixanol ultracentrifugation, the potency of the AAVX purified vectors was comparable with that of iodixanol purified vectors both in vitro and in vivo. Finally, optimization of the purification protocol resulted in a process with an overall efficiency of 65%–80% across all scales and AAV serotypes tested. These data establish AAVX affinity chromatography as a versatile and efficient method for purification of a broad range of AAV serotypes.